Clinical Characteristics and Surgical Prognosis of Hepatocellular Carcinoma with Bile Duct Invasion - Ke-Wei Meng; Mei Dong; Wei-Guo Zhang; Qing-Xian Huang (Gastroenterology Research and Practice)
Objectives. Bile duct invasion (BDI) is a rare event in hepatocellular carcinoma (HCC). The present study aimed at investigating clinical characteristics and surgical outcome of HCC patients with bile duct invasion. Methods. 413 patients with HCC undergoing curative surgery were divided into two groups with (B+) and without BDI (B−). BDI was further classified as central type (B1) and peripheral type (B2). Survival was compared, and risk factors affecting prognosis were identified. Results. 35 (8.5%) patients were diagnosed BDI. Total bilirubin was significantly higher in B+ group than in B− group (P<0.001). Multiple lesions and large nodules (>5 cm) were predominantly identified in B+ group (P<0.01, resp.). Portal vein invasion was more frequently observed in B+ than in B− group (P=0.003). Univariate and multivariate analyses identified central BDI as a significant factor affecting prognosis of HCC patients (risk 1.3, 95% CI 1.1–2.2, P=0.015). The gross overall survival of patients in B+ was significantly worse than in B− (P=0.001), which, however, was not different between B2 and B− (P>0.05). Conclusions. Central but not peripheral BDI was associated with poorer prognosis of HCC patients. Curative surgical resection of tumors and invaded bile duct supplies the only hope for long-term survival of patients.